126k views
1 vote
Solve for x 3(x + 1) = −2(x − 1) − 4

User Matt Ollis
by
5.4k points

2 Answers

5 votes

Answer:

x = -1

Explanation:

3 ( x + 1 ) = -2 ( x - 1 ) - 4

distibute

3x + 3 = -2x + 2 - 4

simplify

3x + 3 = -2x - 2

inverse operations

3x + 3 = -2x - 2

+2x +2x

5x + 3 = -2

-3 -3

5x = -5

/5 /5

x = -1

User Jiyoung
by
6.2k points
6 votes

Answer:

x = -1

Explanation:

distribute:

3x + 3 = -2 (x -1) -4

distribute:

3x + 3 = -2x + 2 - 4

calculate difference:

3x + 3 = -2x - 2

move variable to left and change sign

3x + 2x + 3 = -2

3x + 2x = 2 - 3

collect like terms

5x = -2 - 3

5x = -5

x = -1

User Pouzzler
by
5.1k points